The impact of urban commons in official planning practice: Case study of the former military camp Karatasiou, in Thessaloniki, Greece - Seitanidis, Sokratis; Gritzas, Giorgos (Sens public, 2024)
Amid crisis and austerity, spatial planning in Southern European countries has been used as a ‘prototype’ for new rounds of neoliberalization and a political space that continuously develops through top-down/bottom-up dialectic conflicts. Within this context, planning practice and legislative framework in Greece has focused on attracting direct foreign investments by privatizing big parcels of public property. Despite these restrictive conditions, new partnerships between urban commons and local authorities emerge and highlight the urban commons’ potential as a stakeholder in the planning process. We study the history and interview the key actors of an initially informal community of citizens, who created and manage a space of urban gardening in an urban void, in a former military camp in the metropolitan area of Thessaloniki. They set forth an eco-friendly model of space management based on inclusion and participation. This informal community participated in a network of initiatives and associations, which defended the former military camp area from privatization and demanded its conversion to a green area. A partnership between municipal authorities and urban commons was established and after a long struggle, in December 2020, this partnership achieved a decisive victory against current central government policies: The formal master plan of the area, designating the space as a public green area, was approved by the ministry. Starting from this case study, we discuss the potential of such partnerships in the planning process and how they can change the physical, social and political landscapes surrounding them.